Development of Virgin Coconut Oil (VCO) based emulsion product as dietary supplement - Khor, Yih Phing (2014)
Recently, the demand of virgin coconut oil (VCO) among public continues to rise due to its superior flavour and also its potential health benefits. The present study reports on the development of a VCO-based emulsion product as a dietary supplement. This study is divided into four major parts, namely, the characterisation of commercial food supplement emulsions, the development of VCO-based emulsion formulations, storage stability studies using optimised VCO-based emulsion, and lastly a sensory assessment of an optimised VCO-based emulsion. In the product characterisation study, the physicochemical properties of the commercial emulsion products (C1, C2, C3, and C4) were investigated. C3 exhibited the smallest particle size at 3.25 μm. The pH for the emulsion samples ranged between 2.52 and 3.45 and were thus categorised as acidic. In a texture analysis, C2 was described as the most firm, it was very adhesive and cohesive, and it had high compressibility properties. From a rheological viewpoint, all the emulsion samples exhibited non-Newtonian behaviour, which presented as a shear-thinning property. In this context, the zeta potential of the commercial emulsion samples ranged between -23.17 mV and -52.77 mV. C2 exhibited the highest percentage of fat (18.44%) among all the emulsion samples. During the formulation development of full factorial studies, the influences of different levels of formulation variables, namely the gum arabic concentration (0.75-1.75%, w/v), the xanthan gum concentration (0.8-1.0%, w/v), the VCO concentration (10-20%, v/v), and the maltodextrin concentration (1-3%, w/v) on the pH, particle size, emulsion stability index (ESI), and rheological study of the VCO-based emulsion were studied. All the formulation parameters significantly (p < 0.05) affecting the responses. Two optimal formulations from two different sets of full factorial studies were reported to be 0.8% (w/v) xanthan gum, 1.0% (w/v) gum arabic, 7.5% (v/v) VCO (fixed), and 1% (w/v) maltodextrin (fixed); 0.8% (w/v) xanthan gum (fixed), 1.0% (w/v) gum arabic (fixed), 10% (v/v) VCO, and 2% (w/v) maltodextrin, respectively. Storage stability studies showed that the particle size distributions in the VCO emulsions remained stable throughout the three-month storage period at 25°C and at 50°C. Nevertheless, a phase separation did not occur in either of the VCO emulsion products throughout the storage-stability assessment period. No signs of microbial growth were detected in the emulsion products over the storage period. Furthermore, no significant (p > 0.05) changes in the free fatty acid contents of the emulsion products were observed during storage at 4°C or 25°C throughout the storage period. A sensory assessment among UPM students showed that for the flavouring preference, both 7.5% and 10% VCO emulsion products showed significant differences (p < 0.05) in terms of odour, taste, sweetness, and overall acceptability, and most of the panellists preferred mango flavouring. Among all the emulsion samples, the 7.5% VCO emulsion with mango flavouring yielded the best sensory score with all the sensory attributes scoring more than 5. For the public consumer sensory evaluation, the significant preference towards the VCO emulsion relative to VCO alone also supported the potential to market the VCO emulsion to increase VCO consumption among consumers.